Marvel year by year : a visual chronicle - Marvel Comics Group (London : DK, 2013)
An illustrated chronology of Marvel comics.
Foreword / Stan Lee -- Introduction / Tom DeFalco -- 1939 / Peter Sanderson -- 1940s / Peter Sanderson -- 1950s / Tom Brevoort -- 1960s / Tom DeFalco -- 1970s / Peter Sanderson -- 1980s / Tom DeFalco -- 1990s / Matthew K. Manning -- 2000s / Matthew K. Manning -- 2010s / Matthew K. Manning -- Afterword / Joe Quesada.
Includes index.
Previously published as Marvel Chronicle in the United States in 2008 by DK Publishing.
Keywords: Marvel Comics Group; Marvel Comics Group; Comic books, strips, etc. -- United States -- History; Comic books, strips, etc; United States; History